Integrating Islamic Political Ethics as a Foundation for Bureaucratic Reform: A Narrative Literature Review - Ahmad Yamin (Civiliza Publishing, 2026)
Political development and bureaucratic reform are two interrelated strategic agendas in the effort to realize democratic, accountable, and public interest-oriented governance. This article aims to examine political development as a conceptual framework for bureaucratic reform through a review of the latest literature. This research uses a qualitative approach with library research methods and a narrative literature review design enriched with thematic analysis. Data were obtained from scientific books, reputable national and international journal articles, and relevant policy documents from the past five years. The results of the study indicate that political development is understood as a process of institutionalizing democratic values, the rule of law, public participation, and political accountability, which play a crucial role in shaping a professional and neutral bureaucracy. The literature also reveals the development of bureaucratic reform paradigms, ranging from New Public Management, New Public Governance, to Public Value Governance, which emphasizes that bureaucratic reform cannot be separated from the political context and the quality of democracy. Further analysis shows a reciprocal relationship between political development and bureaucratic reform, where both can either strengthen or weaken each other. However, this study also identified a research gap in the form of a lack of integrative conceptual models that operationally link political development to bureaucratic reform, particularly in developing countries. The findings suggest that Islamic political ethics—centered on the principle of Maslahah (public interest) and the accountability of leaders to both God and society—provide a robust framework for creating a professional, transparent, and service-oriented bureaucracy. This study concludes that integrating these transcendental values into modern administrative systems can strengthen the moral integrity of bureaucrats and ensure more sustainable institutional transformations.